Reduced osteoblast activity in the mice lacking TR4 nuclear receptor leads to osteoporosis - Lin Shin-Jen; Ho Hsin-Chiu; Lee Yi-Fen; Liu Ning-Chun; Liu Su; Li Gonghui; Shyr Chih-Rong; Chang Chawnshang (BMC, 2012)
Abstract Background Early studies suggested that TR4 nuclear receptor might play important roles in the skeletal development, yet its detailed mechanism remains unclear. Methods We generated TR4 knockout mice and compared skeletal development with their wild type littermates. Primary bone marrow cells were cultured and we assayed bone differentiation by alkaline phosphatase and alizarin red staining. Primary calvaria were cultured and osteoblastic marker genes were detected by quantitative PCR. Luciferase reporter assays, chromatin immunoprecipitation (ChIP) assays, and electrophoretic mobility shift assays (EMSA) were performed to demonstrate TR4 can directly regulate bone differentiation marker osteocalcin. Results We first found mice lacking TR4 might develop osteoporosis. We then found that osteoblast progenitor cells isolated from bone marrow of TR4 knockout mice displayed reduced osteoblast differentiation capacity and calcification. Osteoblast primary cultures from TR4 knockout mice calvaria also showed higher proliferation rates indicating lower osteoblast differentiation ability in mice after loss of TR4. Mechanism dissection found the expression of osteoblast markers genes, such as ALP, type I collagen alpha 1, osteocalcin, PTH, and PTHR was dramatically reduced in osteoblasts from TR4 knockout mice as compared to those from TR4 wild type mice. In vitro cell line studies with luciferase reporter assay, ChIP assay, and EMSA further demonstrated TR4 could bind directly to the promoter region of osteocalcin gene and induce its gene expression at the transcriptional level in a dose dependent manner. Conclusions Together, these results demonstrate TR4 may function as a novel transcriptional factor to play pathophysiological roles in maintaining normal osteoblast activity during the bone development and remodeling, and disruption of TR4 function may result in multiple skeletal abnormalities.